Evaluation of alpha-cypermethrin for the control of mites in laying hens under laboratory conditions - Rodríguez García, Daisy (2021)
The aim of the study was to evaluate doses of alphacypermethrin for the control of the mite Pterolichus obtusus in laying hens under laboratory conditions. The experiment was carried out in the experimental houses of the Poultry Research Institute, Cuba, between June and July 2019. In total, 115 White Leghorn laying hens, 52 weeks old, naturally infested with the mite, were used. An initial sampling was carried out on all the birds to determine the levels of infestation and distribute them in homogeneous groups. Four doses of alphacypermethrin (1, 2, 5 and 10 ml/l) were tested by spray baths and compared with a group treated with cypermethrin (12 ml/l) and a control group. Three baths were carried out on a weekly basis. The effectiveness of the treatments was evaluated between 24- and 48-hour post-treatment. Alphacypermethrin in doses of 1 and 2 ml/l was ineffective, while in doses of 5 and 10 ml/l was highly effective. Cypermethrin at a dose of 12 ml/l was highly effective from the second bath.